A study on the records retention and disposition practices of the Commission on Higher Education - Manahan, Mary Joy B.; Rey, Emma M. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2009)
The Commission on Higher Education (CHED) is an important government agency that carries out different functions and responsibilities in the higher education sector of the country. It consequently accumulates voluminous records which are created, received, maintained and used in its numerous transactions. These records serve as the essential building blocks for the Commission's effective service delivery. This study examined the record-keeping practices of the /commission, specifically its records retention and disposition practices. Good record-keeping practices affects the Commission's level of efficiency and efficacy (or inefficiency/inefficacy) in the performance of its duties and responsibilities.
The main objective of the study is to describe the current records retention and disposition practices of the Records Section of the Commission - from inventory, appraisal, retention and disposal, up to the organization, access, retrieval and protection of vital records. The data gathered from the interview with the records clerk of the Records Section, the ocular inspections and observations in the Records Section revealed that: (a) since the establishment of the Records Office of the Commission in 1994, it has yet to conduct a comprehensive inventory of its records; what has been practiced is a records inventory that is limited to a listing of all records that the Commission has created and received in a record book/logbook; (b) the Commission practices appraisal of records but there are no clear guidelines and criteria in assessing the values of the records; (c) the Commission follows no Records Retention and disposition Schedule (RRDS); (do most of the records of the Commission are arranged chronologically, regardless of the title and topic of the records; the office also uses control systems/finding aids such as compiled guides, index cards and record books/logbooks when locating and retrieving records and lastly; (e) the Commission provides a special room with controlled access and is relatively small for storing its vital records which include the significant and confidential records of the Commission.
This study concluded that the Commission needs to establish a records management program that would aid in their record-keeping processes. The following recommendation were formulated and designed by the researcher for the Record Section of the Commission to the Commission to assist the records clerks/officers in improving their records-keeping practices: (1) development of Records Management Committee; (2) development of Records Management Policy; (3) conducting an inventory of records; (4) creation of appraisal guidelines; (5) development of a RRDS and; (6) staff training on records management.
Finally, the researcher conducted an inventory of records of the Commission which led to the identification of the record series, volume of the collection, arrangement and location of records. Through the inventory, the researcher was able to develop a Proposed RRDS for the Commission which is in line with the National Archives of the Philippines' (former Records Management and Archives Office) General Records Disposition Schedule.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Records management